Productivity and Financial Analysis of Fishing Effort with Handline at Kutaraja Oceanic Fishing Port Aceh Province - Angga Setia Manalu; Jonny Zain; Arthur Brown (Tropical Marine Enviromental Sciences, 2023)
Production of catches on hand line fishing gear at Kutaraja Ocean Fishing Port has declined. This is seen from the level of fish production produced, which was 2.407.580 tons in 2018, compared to in 2019 which was 2.285.750 tons. The fishing business, which has become one of the livelihoods of the Indonesian people, is a little riskier than other businesses because the fish, which are the play target of this business, are constantly moving dynamically. The research objective was to determine productivity per GT, Trip, and ABK on hand line fishing gear and to determine the financial feasibility analysis of fishing effort on hand line fishing gears at Kutaraja Ocean Fishing Ports. The benefits of this research are to increase knowledge and insight regarding productivity and financial analysis of the fishing line effort. The method used in this study is a survey method. The data analysis method used in this research is descriptive. The results showed that the value of productivity per trip with large-size ships has a high amount of production compared to smaller ship sizes. Hand line fishing with a vessel size >30 GT has a relatively long payback period, <5 years. While ships with a height of 5 GT, 6 GT, 9 GT, 22 GT, and 24 GT have a payback period of <3 years